Validation of a Model for Measuring Digital Literacy, Student Engagement, and Learning Motivation - Febrina Welianis; Zul Afdal (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2026)
To provide high-quality research data, research tools' validity and dependability are essential. A measurement model of digital literacy, student engagement, and learning motivation among high school students was validated in this study using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The students took part in this quantitative investigation's instrument piloting phase. Data was gathered using a five-point Likert scale questionnaire, and analysis was done using SmartPLS 4. The model was assessed using convergent validity, discriminant validity, and construct reliablity. The study's findings show that every construct satisfies the suggested standards for validity and reliability.The outer loading values were within acceptable bounds, the Composite Reliability and Cronbach's Alpha values were greater than 0.60, and the Average Variance Extracted (AVE) was greater than 0.50. These results imply that the assessment methods for learning motivation, student engagement, and digital literacy are appropriate for use in educational research. In the context of high school pupils, this study offers empirical support for the viability of a measurement model that incorporates these three constructs.